Prognostic value of the TGFβ1 rs4803455 single nucleotide polymorphism in small cell lung cancer. Issue 3 (June 2021) - Ayala de Miguel, Pablo; Enguix-Riego, María Valle; Cacicedo, Jon; Delgado, Blas David; Perez, Marco; Praena-Fernández, Juan Manuel; Quintana Cortés, Laura; Borrega García, Pablo; del Campo, Eleonor Rivin; Lopez Guerra, Jose Luis
Background: Small cell lung cancer (SCLC) is one of the greatest therapeutic challenges of oncology. Potential associations between single nucleotide polymorphisms in heat shock protein β1 (HSPB1) and transforming growth factor β1 (TGFβ1) and survival have been investigated. Methods: A prospective multicenter study of 94 patients with SCLC treated between 2013 and 2016 was conducted. Clinical, tumour-related, therapeutic, and genetic (9 SNPs of TGFβ1 gene and 5 of HSPB1 gene) variables were analyzed. Results: The cohort included 77 men and 17 women with a median age of 61 years. Eighty percent presented with limited stage at diagnosis and received thoracic radiation with a median dose of 45 Gy (twice-daily radiation in 42%). Forty-seven percent received concurrent platinum-based chemotherapy and 57% received prophylactic cranial irradiation (PCI). Overall survival (OS) was 34% at 2 years and 16% at 3 years. In multivariate analysis, the rs4803455:CA genotype of the TGFβ1 gene showed a statistically significant association with lower disease-free survival (DFS; hazard ratio [HR] 3.13; confidence interval [CI] 1.19–8.17; p = 0.020) and higher local recurrence (HR 3.80; CI 1.37–10.5; p = 0.048), and a marginal association with lower OS (HR 1.94; CI 0.98–3.83; p = 0.057). A combined analysis showed that patients receiving PCI and carrying the rs4803455:CA genotype had statistically significant lower OS ( p < 0.001) and DFS ( p < 0.001) than patients receiving PCI and carrying the rs4803455:AA genotype. Conclusions: Genetic analysis showed the CA genotype of TGFβ1 SNP rs4803455 was associated with worse prognosis in patients with SCLC and could be considered as a potential biomarker.